Annapolis Royal, Nova Scotia, collection
Volume (24 pages) containing correspondence, instructions, commissions, and other papers, chiefly contemporary copies, relating to Sir Francis Nicholson's successful military expedition against the French at Port Royal, Nova Scotia, later renamed Annapolis Royal in honor of Queen Anne. Includes Nicholson's commission as commander in charge of Her Majesty's Forces, letter of Gov. Joseph Dudley to the Council and Representatives in New Hampshire, and minutes of various councils of war. Other individuals figuring prominently in the papers include Samuel Cranston, Gurdon Saltonstall, Lord Sunderland, and Samuel Vetch.
Microfilm edition available
Microfilm produced from material, chiefly transcripts, in the Manuscript Division.
Chiefly contemporary handwritten transcripts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Forms part of: Peter Force papers and collection (Series 8D : entry 6).
Keywords: Cranston, Samuel, -- 1659-1727.; Dudley, Joseph, -- 1647-1720.; Nicholson, Francis, -- 1655-1728.; Saltonstall, Gurdon, -- 1666-1724.; Sunderland, Charles Spencer, -- Earl of, -- 1674-1722.; Vetch, Samuel, -- 1668-1732.; Great Britain. -- Army -- Colonial forces -- America; Canada -- History -- To 1763 (New France); Nova Scotia -- History -- 1603-1713.